2013
DOI: 10.1155/2013/205692
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns of Placental and Paraovarian Adrenocortical Heterotopias Are Different

Abstract: Two cases of adrenocortical heterotopia are reported. One is in a full-term placenta. The other is adjacent to the ovarian hilum of an adult. Both are incidental findings. Despite sharing similar histological and immunological features, they show different growth patterns. The literature is reviewed and adrenocortical heterotopias of different locations are compared. New hypotheses of its histogenesis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…22 Rare microscopic nodules of adrenocortical tissue have been described in the human placenta. 1,2,610 Including the initial report in 1980 by Cox and Chavrier, 7 11 cases of adrenocortical heterotopia of the placenta have been reported in 7 manuscripts. Three of these reports have used immunohistochemistry on single cases to support the concept of adrenocortical differentiation, 1,2,10 the remaining 8 cases were diagnosed by morphology alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…22 Rare microscopic nodules of adrenocortical tissue have been described in the human placenta. 1,2,610 Including the initial report in 1980 by Cox and Chavrier, 7 11 cases of adrenocortical heterotopia of the placenta have been reported in 7 manuscripts. Three of these reports have used immunohistochemistry on single cases to support the concept of adrenocortical differentiation, 1,2,10 the remaining 8 cases were diagnosed by morphology alone.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,610 Including the initial report in 1980 by Cox and Chavrier, 7 11 cases of adrenocortical heterotopia of the placenta have been reported in 7 manuscripts. Three of these reports have used immunohistochemistry on single cases to support the concept of adrenocortical differentiation, 1,2,10 the remaining 8 cases were diagnosed by morphology alone. 69 The earliest study with immunohistochemistry demonstrated granular cytoplasmic reactivity for rabbit antisera to DHEA-sulfate in the nodule.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations